2006
DOI: 10.1210/me.2005-0328
|View full text |Cite
|
Sign up to set email alerts
|

Codependence of Growth Hormone-Responsive, Sexually Dimorphic Hepatic Gene Expression on Signal Transducer and Activator of Transcription 5b and Hepatic Nuclear Factor 4α

Abstract: Targeted disruption of the signal transducer and activator of transcription 5b gene (STAT5b) leads to decreased expression in male mouse liver of a male-predominant cytochrome (Cyp) 2d protein, whereas female-predominant Cyp2b proteins are increased. Presently, we characterize the effects of STAT5b deficiency on 15 specific, individual Cyp RNAs and other sexually dimorphic liver gene products. All seven male-specific RNAs investigated were decreased to normal female levels in STAT5b-deficient male liver, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
139
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(154 citation statements)
references
References 67 publications
12
139
0
3
Order By: Relevance
“…every 3.5-4 h in direct response to each plasma GH pulse in the adult male rat [16,17], raising the possibility that STAT5b-and HNF4α-stimulated transcriptional events may both be influenced by the pulsatile, male plasma-GH rhythm. This latter possibility is consistent with the sex-dependent effects that HNF4α has on certain GH-dependent hepatic genes [6,12]. In the present study, HNF4α has been shown to inhibit STAT5b transcriptional activity by blocking STAT5b tyrosine phosphorylation that is catalysed by the GH-receptor-associated tyrosine kinase JAK2.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…every 3.5-4 h in direct response to each plasma GH pulse in the adult male rat [16,17], raising the possibility that STAT5b-and HNF4α-stimulated transcriptional events may both be influenced by the pulsatile, male plasma-GH rhythm. This latter possibility is consistent with the sex-dependent effects that HNF4α has on certain GH-dependent hepatic genes [6,12]. In the present study, HNF4α has been shown to inhibit STAT5b transcriptional activity by blocking STAT5b tyrosine phosphorylation that is catalysed by the GH-receptor-associated tyrosine kinase JAK2.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study we have characterized bi-directional crosstalk between STAT5b and HNF4α, which both play important roles in liver gene expression, in particular sex-dependent, GHregulated gene expression, as revealed by the analysis of knockout mouse models [6,12,21]. We also demonstrate that STAT5b enhances HNF4α-dependent gene transcription, while HNF4α is shown to inhibit GH-stimulated STAT5b tyrosine phosphorylation, nuclear translocation and transcriptional activity.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations